Implementasi Custumer Relationship Management (CRM) pada Pelaku UMKM - M. Adi Trisna Wahyudi; Agus Hermawan; Moh. Ilham (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This research investigates the implementation of Customer Relationship Management (CRM) in the Micro, Small and Medium Enterprises (MSME) and startup sectors. Through a qualitative approach, data was collected from a number of MSMEs and startups to analyze the factors that influence the adoption and success of CRM implementation. The findings show that limited resources, lack of knowledge about the benefits of CRM, and dependence on technological infrastructure are the main challenges in adopting CRM systems. However, CRM has also been found to have great potential in increasing customer retention, developing more suitable products, and expanding into new markets. Practical implications of these findings include recommendations for appropriate resource allocation, employee training, and more effective digital marketing strategies. The contribution of this research lies in a deeper understanding of CRM implementation in the context of MSMEs and startups as well as practical guidance for improving business performance through effective CRM strategies.